2022
DOI: 10.3390/bios12050330
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Microfluidic Device Integrated with Electrochemical Impedance Spectroscopy for Cell-Based Immunoassay

Abstract: The dynamic immune response to various diseases and therapies has been considered a promising indicator of disease status and therapeutic effectiveness. For instance, the human peripheral blood mononuclear cell (PBMC), as a major player in the immune system, is an important index to indicate a patient’s immune function. Therefore, establishing a simple yet sensitive tool that can frequently assess the immune system during the course of disease and treatment is of great importance. This study introduced an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 52 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…A gold layer was deposited on an ITO substrate with electron-beam physical vapor deposition, peeled, etched to create IDEs, and finally coated with anti-45 on the gold IDEs to manufacture a biometric layer. The detection of different concentrations of PBMCs in dynamic and static cell culture modes was compared in this system, and the results showed that the dynamic mode had a higher sensitivity than the PBMCs in the static condition [104]. Both electrochemical biosensors and microfluidics have their specific benefits, so the rational integration of these two analytical devices will create greater functional platforms.…”
Section: Discussionmentioning
confidence: 99%
“…A gold layer was deposited on an ITO substrate with electron-beam physical vapor deposition, peeled, etched to create IDEs, and finally coated with anti-45 on the gold IDEs to manufacture a biometric layer. The detection of different concentrations of PBMCs in dynamic and static cell culture modes was compared in this system, and the results showed that the dynamic mode had a higher sensitivity than the PBMCs in the static condition [104]. Both electrochemical biosensors and microfluidics have their specific benefits, so the rational integration of these two analytical devices will create greater functional platforms.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical impedance spectroscopy (EIS)-based detection utilizes the contrast of impedance between different objects to achieve the detection and has been widely applied in microfluidic systems to characterize particles and cells [ 54 , 55 , 56 , 57 , 58 ]. The typical detection setup contains planar sensing electrode patterns deposited on the glass substrate (sometimes with an inert interstitial layer to isolate electrodes from the solution, thereby reducing electrode polarization) underneath the microfluidic channel [ 59 ].…”
Section: Detection Methodsmentioning
confidence: 99%
“…The authors validated the system with two chemotherapeutic drugs, DDP and epirubicin (EPI), towards MDA‐MB‐231 breast cancer cells and MCF‐10A normal breast cells. Recently, Zhang and Liu [ 197 ] developed digital microfluidics, including an electrochemical impedance spectroscope (EIS)‐based biosensor to detect human peripheral blood mononuclear cells to profile immune‐mediated therapeutic responses.…”
Section: Recent Advances In Microfluidics‐based Cell Culture Devices ...mentioning
confidence: 99%